Detection, characterization and pathogenicity of citrus viroids in Peninsular Malaysia - Khoo, Ying Wei (2017)
Citrus from Rutaceae family is a nutritious fruit that traded globally. Citrus viroids are known to pose a threat to citrus production. These viroids are distributed worldwide, but yet to be reported in Malaysia. Lack of information on citrus viroids in Malaysia is of concern for the local citrus production. In view of this, the objectives of this study were (a) to detect and characterize citrus viroids in Peninsular Malaysia using Multiplex RT-PCR, RT-PCR, cloning and sequencing, (b) to test the pathogenicity and to determine host range of the citrus viroids on seedlings of lemon, chili pepper, cucumber, tobacco and tomato. Leaves from 133 citrus plants showing viroid-like symptom such as stunting, leaf bending, leaf epinasty, leaf necrosis, leaf yellowing and petiole necrosis in Johor (Muar), Malacca (Cheng), Pahang (Jaya Gading, Sri Damai and Semambu), Perak (Bagan Serai and Kamunting) and Selangor (Kuala Selangor, Sabak Bernam, Serdang and Kajang) were collected. Complementary DNA of samples was synthesized using random hexamer by Avian Myeloblastosis Virus Reverse Transcriptase (AMV-RT). Multiplex RT-PCR was performed to detect Citrus exocortis viroid (CEVd), Citrus bent leaf viroid (CBLVd), Hop stunt viroid (HSVd) and Citrus dwarfing viroid (CDVd) using specific primer sets of these viroids. Results of molecular detection by Multiplex RT-PCR showed that 23 samples were positive for CBLVd but not CEVd, HSVd and CDVd on Citrus aurantifolia, C. hystrix, C. jambhiri, C. maxima, C. microcarpa and C. sinensis from Johor, Malacca and Selangor respectively. CBLVd was detected in 17.3% out of the total sample. RT-PCR was carried out to amplify the full length of CBLVd using CBLVd specific primer sets. The amplicons were cloned and sequenced. Sequence analysis of 12 clones showed that the CBLVd isolates from this study were 328 nt in size with 99-100% of sequence homology to CBLVd isolate Jp (AB006734). Of total 12 clones, substitution mainly occurred in the Pathogenicity and Variable domains of the secondary structure of seven isolates. Results from phylogenetic analysis of the Malaysian CBLVd isolates with isolates from China, Japan, Pakistan and Spain showed that the Malaysian isolates formed same clade with Japan isolates (AB006734). Pathogenicity study showed that lemon seedlings inoculated with plasmid containing a CBLVd insert (MyMuar01/14) expressed symptoms such as leaf epinasty, leaf bending, leaf yellowing and midvein necrosis over a 12 month observation period. No stunting expressed in CBLVd inoculated lemon seed-grown seedlings over 12 months. CBLVd were detected in 1, 2 and 3 month inoculated lemon seedlings between 3 to 6 months post-inoculation by RT-PCR assay. Cloning and sequencing of the amplicons showed the presence of CBLVd with more than 99% sequence similarity with CBLVd variant (MyMuar01/14) that was used for the inoculation. Host range study showed that chili pepper, cucumber, tobacco and tomato were not suitable alternate host for CBLVd as there were no symptoms expressed during 3 month post-inoculation observation. RT-PCR assay also failed to detect the CBLVd RNA in the host tested. In summary, CBLVd was detected in citrus grown in Peninsular Malaysia. Twenty-three citrus plants that included C. microcarpa, C. maxima, C. aurantifolia. C. hystrix and C. sinensis and C. jambhiri were positve for CBLVd. In this study, the CBLVd variants were in size of 328 nt and had 99-100% similarity with CBLVd isolate Jp. Substitution of nucleotide of CBLVd variants in this study occurred in mainly P and V domain. CBLVd isolate Malaysia formed same clade with Japan isolates. CBLVd replicated in lemon seedlings with expressed symptoms, but no sign of stunting over 12 months. CBLVd did not replicate in chili pepper, cucumber, tobacco and tomato during 2 month post-inoculation. This is the first report of CBLVd variants in Malaysia.